Diplomacy, funding and animal welfare - Roeder, Larry Winter; Rimondini, Michela; SpringerLink (Online service). (Berlin, Heidelberg Springer Berlin Heidelberg, 2011)
Diplomacy, Funding and Animal Welfare is a practical guide to the best diplomatic and negotiation practices needed to convince governments and international institutions to effectively protect animals, which also introduces new approaches to fundraising.  Animal protection advocates are prepared for speaking to diplomats and government officials in any setting, and to combatants in war zones.  The book mainly focuses on approaching local and national governments, the United Nations system, the international Red Cross movement and systems related to other international organizations that can help animals, often in surprising ways.  The reader will learn the rules of ?diplomatic protocol", and much about the rules and procedures of major international bodies.  To provide balance and real world relevance, the guide draws on a compilation of the author?s extensive activities across a range of development, animal welfare, emergency management and climate issues in government and in the NGO world, as well as interviews with scholars and officials from NGOs, diplomatic missions, the United Nations, the Red Cross, governments and corporations.
Diplomatic Theory and Practice.-  International Funding for Animal Protection -- International Conferences and Delegation Management -- Protocol -- The Media as a Tool for Diplomacy -- Important Associations and International Organizations -- Epilogue.
Electronic reproduction.
Keywords: Animal welfare; International relations; Animal welfare -- Economics; Animal rights; Internationally; Electronic books